MENINGKATKAN HASIL BELAJAR MATEMATIKA MELALUI METODE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) PADA SISWA KELAS V - Syahrul Deska Ramadhani; Binti Khoiriyah; Pixyoriza (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The low learning outcomes of students in Mathematics are caused by the learning process which is still centered on the teacher resulting in a lack of student involvement in the learning process. This study aims to improve the learning outcomes of Mathematics on the material of geometric nets through the Student Teams Achievement Division (STAD) method in fifth grade students of UPTD SD Negeri 1 Tambah Subur. The method used is classroom action research (CAR). The sample in this study was 28 fifth grade students. The sampling technique was purposive sampling. Data collection techniques were observation, interviews, tests, and documentation. The results showed that the application of the Student Teams Achievement Division (STAD) method can improve student learning outcomes, marked by an increase in the percentage of learning completeness from 60% in cycle I to 85% in cycle II, resulting in an increase of 25%. Thus, the Student Teams Achievement Division (STAD) learning method can improve the learning outcomes of fifth grade students of UPTD SD Negeri 1 Tambah Subur